Patient Profile and Diagnostic Distribution in a Turkish Rheumatology Outpatient Clinic: A Prospective 2-Month Analysis - Selin Cilli Hayıroğlu; Ender İğneci (The Eurasian Journal of Medicine, 2026)
Background: This study aimed to evaluate the clinical and demographic profile of patients attending a rheumatology outpatient clinic in Türkiye over a 2-month period, with a focus on symptom distribution, visit types, and rheumatologic diagnostic outcomes. Methods: This prospective cross-sectional study was conducted at a rheumatology outpatient clinic in Türkiye. A total of 971 patients were included over a 2-month period. Patients were categorized as follow-up (n = 491), newly diagnosed (n = 45), or other/first visit (n = 435). Demographic data, presenting symptoms, laboratory findings, and final diagnoses were recorded. Results: The mean age of the cohort was 51.3 years (median: 53 years), and 74.0% were female (n = 719). Among the 480 patients without a prior rheumatologic diagnosis, the most common presenting symptom was peripheral joint pain (55.8%), followed by low back pain (7.9%) and myalgia (7.5%). Of these, 45 (9.4%) received a new rheumatologic diagnosis. Overall, 55.2% of all patients (n = 536) carried a rheumatologic diagnosis. Among patients with a rheumatologic diagnosis, the most frequent were rheumatoid arthritis (30.4%), ankylosing spondylitis (13.9%), and Sjögren syndrome (8.9%). Compared to patients without a diagnosis, newly diagnosed patients had significantly higher rates of myalgia, arthritis, elevated acute phase reactants, Raynaud’s phenomenon, and abdominal pain (P < .05). Conclusion: This study provides a comprehensive snapshot of the rheumatology outpatient population in Türkiye. Peripheral joint pain is the predominant presenting complaint, and over half of patients carry an established rheumatologic diagnosis. Identifying symptom patterns associated with new diagnoses may facilitate earlier recognition and referral in clinical practice. Cite this article as: Cilli Hayıroğlu S, İğneci E. Patient profile and diagnostic distribution in a Turkish rheumatology outpatient clinic: a prospective 2-month analysis. Eurasian J Med. 2026, 58(4), 1504, doi: 10.5152/eurasianjmed.2026.261504.